Implementasi Model Pembelajaran Mind Mapping dengan Media Gambar untuk Meningkatkan Pemahaman Peserta Didik pada Materi Menerima Qadha dan Qadar di SD Negeri 005 Malinau Kota - Abidin, Zainal; Sholihah, Nining Nikmatush; Rasyid, Fathor (Allimna: Jurnal Pendidikan Profesi Guru, 2024)
This research is entitled: "Implementation of the Mind Mapping Learning Model with Image Media to Improve Students' Understanding of the Material of Receiving Qada and Qadar. The aim of this research is to Improve Learning Results for Receiving Qada and Qadar Using the Mind Mapping Learning Model with Image Media for Class VI State Elementary School Students 005 Malinau City. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation and reflection. Based on the results of action research, the Mind Mapping Learning Model with Image Media can Improve Learning Outcomes on Receiving Qada and Qadar Image Material for Class VI Students at SD Negeri 005 Malinau City. Furthermore, the researcher recommends: (1) Teachers who experience the same difficulties can apply the Mind Mapping Learning Model with Image Media to improve Learning Outcomes. (2) In order to get maximum results, teachers are expected to make the Mind Mapping Learning Model using Image Media more interesting and varied.